Behavior of Patients with Chronic Kidney Disease - Kurniawaty, Yuni; Lestarina, Ni Nyoman Wahyu; Kristama, Baswara Yua (Jurnal Keperawatan, 2020)
Background: CKD patients increase with increasing age prevalence of 15.8%. Changes in behavior in people with CKD focus on diet, physical activity, quality of life, fatigue, knowledge, self-efficacy and self-management. Method: This research is qualitative with phenomenological methods. The subjects were 12 informants with CKD using purposive sampling technique. Data collection was carried out using in-depth and semi-structured interviews in June - August 2019 at William Booth Hospital in Surabaya. Data analysis using Giorgi's phenomenological analysis and thematic analysis then inductively and triangulating data. Results: This study found 4 themes, namely: holistic interpretation of needs, suggestions for healing, understanding of bodily functions and diet disobedience. Conclusion: CKD patients strive to meet their needs holistically with all the limitations of physical conditions by trying to carry out routine the treatment process recommended by health workers, even though barriers come from an understanding of bodily functions that are able to balance in CKD conditions and from the environment such as climate that makes disobedient to a fluid and nutritional diet. Seeing the importance of the impact of compliance with CKD patients in the implementation of CKD treatment management health workers need to make a systematic approach to CKD patients in treatment management